(untitled) (Research, Society and Development, 2023)
Pre-eclampsia is characterized by elevation of systolic blood pressure above 140 mmHg and/or diastolic blood pressure above 90 mmHg after the twentieth week of gestation in previously normotensive women associated with proteinuria or end-organ dysfunction. It has a wide-ranging effect on multiple systems, affecting both maternal and fetal health. The study was based on questioning the changes used in pre-eclampsia screening that allowed an early and accurate diagnosis of the disease. Thus, the present study aims to comparatively analyze the changes over the years and the new adjuvants used in investigations of pre-eclampsia. An integrative literature review was carried out, based on articles published between the years 2000 and 2023 and accessed in the databases: PubMed, BVS, Google Scholar and SciELO. Terminologies registered in the Health Sciences Descriptors (DeCs) were used. It is concluded that it is essential to use methods of prediction and early diagnosis, identifying pregnant women at risk and initiating adequate preventive measures.